Performance and mechanisms exploration of nano zinc oxide (nZnO) on anaerobic decolorization by Shewanella oneidensis MR-1. (October 2022) - Cao, Feng-Ting; Ma, Xiao-Lin; Zhou, Xiang-Tong; Han, Jun-Cheng; Xiao, Xiang
Abstract: Although the ecological safety of nanomaterials is of widespread concern, their current ambient concentrations are not yet sufficient to cause serious toxic effects. Thus, the nontoxic bioimpact of nanomaterials in wastewater treatment has attracted increasing attention. In this study, the effect of nano zinc oxide (nZnO), one of the most widely used nanomaterials, on the anaerobic biodegradation of methyl orange (MO) by Shewanella oneidensis MR-1 was comprehensively investigated. High-dosage nZnO (>0.5 mg/L) caused severe toxic stress on S. oneidensis MR-1, resulting in the decrease in decolorization efficiency. However, nZnO at ambient concentrations could act as nanostimulants and promote the anaerobic removal of MO by S. oneidensis MR-1, which should be attributed to the improvement of decolorization efficiency rather than cell proliferation. The dissolved Zn 2+ was found to contribute to the bioeffect of nZnO on MO decolorization. Further investigation revealed that low-dosage nZnO could promote the cell viability, membrane permeability, anaerobic metabolism, as well as related gene expression, indicating that nZnO facilitated rather than inhibited the anaerobic wastewater treatment under ambient conditions. Thus, this work provides a new insight into the bioeffect of nZnO in actual environment and facilitates the practical application of nanomaterials as nanostimulants in biological process. Highlights: High concentration of nZnO inhibited azo dye degradation by S. oneidensis MR-1. Low-dose nZnO exposure facilitated anaerobic biodecolorization of methyl orange. Anaerobic bioeffect of nZnO depended on the dissolved Zn 2+ . NZnO influenced cell viability, membrane permeability, and anaerobic metabolism. Gene expression of S. oneidensis MR-1 was subjected to nZnO dosage.